HUBUNGAN ANTARA KEPERCAYAAN DIRI DAN POLA ASUH OTORITATIF DENGAN CITRA DIRI PADA MAHASISWI YANG MELAKUKAN PERAWATAN WAJAH DI KLINIK KECANTIKAN - Ulfiyatun Ni’mah; Rohmatun Rohmatun (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2017)
This aims to determine the relationship between self confidence and authoritative parenting with self image female students psychology faculty of sultan agung islamic university doing face treatment in beauty clinic using correlational quantitative method. The population in this study is 96 female students of psychology faculty in sultan agung islamic university doing face treatment in beauty clinic. The sampling method uses saturated sampling. The measuring tool used in this study consists of 3 scales. The self image Scale with moving discrimantion items index were between 0,373 to 0,634 and α = 0,837. The self confidence Scale with moving discrimantion items index were between 0,322 to 0,621 and α= 0.901. The the authoritative parenting Scale with moving discrimantion items index were between 0,313 to 0,697 and α= 0.886 Analysis used multiple regression analysis and partial correlation. The results of the first hypothesis analysis got score of R= 0.686 and Farithmetic= 41,372, P=0.000 (p <0.01) mean a very significant relationship between self confidence and authoritative parenting with self image female students of psychology faculty in sultan agung islamic university doing face treatment in beauty clinic. Result of second hypothesis analysis got score rx1y = 0,354 with significance 0,000 (p <0,01) means a very significant positive relationship between self confidence with self image. The result of the third hypothesis analysis got the score rx2y= 0,3961 with significance 0,000 (p <0,01) means a very significant positive relationship between authoritative parenting with self image female. This aim explains that self-confidence and authoritative parenting provide an effective contribution to self-image 0f 47,1% while 52,9% comes from other factors. Key word: Self-image, Self-confidence, Authoritative parenting